UMA PROPOSTA DE ANÁLISE INTERDISCIPLINAR PARA OS ESTUDOS DO INTEGRALISMO (Revista de História Regional, 2007)
The object of this article is to demonstrate to students of Brazilian Integralism the importance of investing in an interdisciplinary proposal between History and Linguistics, in the field of Discourse Analysis. This analytic perspective becomes even more necessary when one tries to understand the conditions of production of discourses that justified and legitimized the process ofrepression against its members after 1937 when they were removed from the political arena of the Estado Novo.